KEMAMPUAN BERBICARA ANAK USIA 3-4 TAHUN DI KELUARGA MULTIETNIK: (STUDI KASUS DI KECAMATAN DUREN SAWIT, JAKARTA TIMUR) - Dwi Putri, Wara; Hapidin, Hapidin; Akmal, Yenina (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2021)
This qualitative research is to find out and describe The Speaking Ability of 3-4 years old in Multiethnic Family, Duren Sawit, East Jakarta. The subject of this research is a child of 3-4 years old who is in a multiethnic family environment. Collecting data by observation, interview, and documentation. In this research using case study method, with Creswell analysis data techniques. The method consists of description and theme findings, interrelating theme, and interpreting the meaning of theme. The research findings that the ability to speak in children aged 3-4 years is seen in (1) the process of acquiring new vocabulary that occurs due to the interaction carried out by children with family and friends in their home environment, (2) the ability of children to use a variety of languages such us language English, Spanish, and Indonesian when speaking, (3) Disclosures sentences spoken by children already look right for obvious reasons, and (4) Factors for the formation of children's speaking abilities, where children are given freedom and proper direction in adapting to the environment her home.